Effects of diurnal variation and prolonged refractoriness on repeated measurements of airways responsiveness to methacholine. Issue 3 (March 1995) - Beach, J R; Stenton, S C; Connolly, M J; Walters, E H; Hendrick, D J
Abstract : BACKGROUND--A number of studies have suggested that diurnal variation in airways responsiveness underlies the circadian rhythm of ventilatory function in asthma. Measurements of airways responsiveness are therefore often performed at standardised times in order to avoid this possible effect, but this is not practical for epidemiological studies. Refractoriness to methacholine has also been reported and this, too, could confound the results of methacholine tests repeated over short intervals. This investigation was carried out to evaluate the possible magnitude of diurnal variation and refractoriness in repeated measures of airways responsiveness to methacholine. METHODS--To investigate diurnal variation in airways responsiveness, 24 asthmatic subjects aged 18-45 underwent five methacholine tests over three days which were not necessarily consecutive: day 1 at 08:00 hours; day 2 at 08:00 hours, 14:00 hours, 20:00 hours; day 3 at 20:00 hours. To investigate refractoriness a retrospective analysis was undertaken of all paired methacholine tests performed in individuals within our unit between 1984 and 1990 where there had been no intervention likely to affect the results. RESULTS--The first investigation revealed no diurnal change in airways responsiveness although there was a change in FEV1. Mean PD20 did, however, increase 1.57 fold from 08:00 hours on day 1 to 08:00 hours on day 2 for subjects studied on consecutive days. The second investigation confirmed that a test interval of up to 24 hours (but not of 48 or more hours) was associated with a refractory index (PD20 test 2/PD20 test 1) of > 1. CONCLUSIONS--No diurnal variation in airways responsiveness was detected for measurements made between 08:00 hours and 20:00 hours, but an interval between successive tests of up to 24 hours was associated with refractoriness. Diurnal variation is not likely to exert an important confounding effect on methacholine tests carried out between 08:00 hours and 20:00 hours, but confounding could result from refractoriness if tests are repeated at intervals up to 24 hours.